Drone GPS data analysis for flight path reconstruction: A study on DJI, Parrot & Yuneec make drones. (September 2021) - Kumar, Ravin; Agrawal, Animesh Kumar
Abstract: In past few years, the technological growth in field of drones has not only offered multiple opportunities, but has also thrown numerous threats and challenges. Drone is a potential weapon in itself and can be used to carry out a targeted attack, carry out reconnaissance, smuggling of arms/drugs, etc. Due to cheap and easy availability of commercial drones in the market, the security threat posed by the drones has increased manifold. Additionally, the possibility of customization and option of assembling a drone by an individual makes it an even bigger threat. Unfortunately it is difficult to completely restrict/stop use of such aerial platforms by malicious actors. Therefore there is a need to develop techniques and procedures in the field of drone forensics to be able to extract and accurately analyse the positioning data, provide valuable tactical information about flight take-off location, flight path taken and reconstruct the flight operation, if required. The study in this paper aims at extracting and analysing GPS data from three different drone models belonging to three different families, followed by representing the positioning data as flight path. This paper also introduces a newly developed utility tool named "FlyLog Converter Tool" which processes and converts the.txt/.json flight log of Parrot make drones into easily understandable.csv format. Highlights: This paper is aimed on carrying out digital forensics analysis using open source tools on the Navigational Data of Drones. Extraction and analysis of flight logs and navigational data is important from forensic point of view. This analysis is required to be complimented with visual representation of drone flight path for better appreciation. This paper introduces a newly developed utility tool named "FlyLog Converter Tool" to process flight logs of Parrot Drones. Flight Data analysis on three different drones provides insight on the type and content of different flight logs.